The Effect of Celebrity Instagram Endorsment on Impulsive Buying Behavior in Students in Rokan Hulu Regency, Riau Province - Triyani Capeg Hadmandho (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The use of Instagram as a digital marketing medium has become increasingly popular since the emergence of the microcelebrity phenomenon or commonly referred to as Instagram celebrity (celebgram). In Indonesia, the use of celebrity endorsements has increased rapidly and has become a trend in the online business world. Impulse buying is one of the unique characteristics possessed by the Indonesian people, namely purchases that are made spontaneously, without planning and without careful consideration. Despite the fact that more and more companies or online business people are using the services of celebgrams for endorsements, scientific knowledge about the effect of celebgram endorsements on impulsive buying behavior is still limited. This study only focuses on endorsement programs for fashion products and impulse buying. This study makes a new contribution to the importance of celebrity endorsements in encouraging impulse buying behavior and provides insights for further research on a larger scale. The purpose of this study was to determine the effect of celebrity instagram endorsements on impulsive buying behavior in students in Rokan Hulu Regency, Riau Province. This study used a sample of 100 students who were selected using non-probability sampling technique. The survey method was conducted with a questionnaire strategy, male and female respondents were given the same questionnaire. The resulting data will be analyzed using the SPSS program. The analytical tool used is Multiple Linear Regression by performing classical assumption tests (Normality Test, Heteroscedasticity, Multicollinearity Test), and Hypothesis Testing (F Test, t Test and Coefficient of Determination Test). In this study, the output is targeted in the form of an accredited national journal. Description of TKT The proposed research is at level 2.